Assessment of uptake of intermittent preventive treatment of malaria among pregnant women attending antenatal clinic in public health facilities in Osogbo metropolis, Osun state, Nigeria - Moridiyat Omolara Adeyinka Adeyemo; Ganiyat Odunola Adeniran; Victoria Adenike Adeniyi; Elisha Oluwatobi Olabisi; Rahmat Aderayo Oyekale; Oladayo Akinwale; Sakirat Folasade Adejare; Omodolapo Justinah Olaleye; Rosemary Omolara Fafowora; Busayo Temilola Akinbowale (Elsevier, 2024)
Background: WHO recommends three or more doses of intermittent preventive treatment of Malaria with Sulfadoxine Pyrimethamine (IPTp-SP) for pregnant women living in areas of moderate-to-high malaria transmission in Africa to protect them and their babies from severe risks by malaria. Despite this, the coverage of utilization of a minimum of three doses of the drug is still very low in Nigeria. This study assessed the knowledge and utilisation of IPTp-SP among pregnant women attending antenatal clinics in public health facilities in Osogbo, Nigeria. Methods: Descriptive cross-sectional was used, data were randomly collected from 549 respondents through a semi-structured self-administered questionnaire. Descriptive statistics, Pearson chi-square, and logistic regression were used for analysis. Results: About half (49.4%) of the respondents had good overall knowledge of IPTp-SP, 72.2% took a minimum of one dose, and only 10.1 % took a minimum of three doses. Factors influencing the utilisation included drug affordability, SP shortage at the facility, and monitoring of pregnant women's intake of SP. Logistic regression analysis indicated that pregnant women in primary and secondary healthcare settings were 2.4 times and 1.3 times respectively more likely to utilise IPTp than those in tertiary healthcare settings.Conclusion and recommendation.Almost half of the participants had good knowledge of IPTp-SP, only a few took four doses. Healthcare providers should organize IEC programmes to create more awareness among the public on the use and safety of SP in pregnancy. The government is to establish a mechanism to ensure a consistent supply of SP in all healthcare settings,